SERAPAN HARA N DAN P PADA TANAMAN CIPLUKAN (Physalis angulata L.) YANG DIPERLAKUKAN DENGAN BERBAGAI MACAM PUPUK KANDANG - Septiana, Nurul Aini; Kusmarwiyah, Kusmarwiyah; Silawibawa, I Putu (CROP AGRO, Scientific Journal of Agronomy, 2023)
This study was aimed to determine the influence of various kinds of manure on N and P uptake on Golden berry (Physalis angulata L.). The experiment was conducted in a plastic house in Terong Tawah, Subistrict of Labuapi, West Lombok regency. The experiment was set up using a Completely Randomized Design (CRD) with 6 treatments namely A0 (control), A1 (chicken manure), A2 (goat-manure, A3 (buffalo manure), A4 (horse manure), and A5 (cattle manure) which were repeated 3 times. The results showed that application of manures significantly affect fresh weight of stover, the dry weight of stover, N and P uptake. The application of buffalo manure tend to have the highest nutrients uptake.